Is ICSI Risky? - May Y. W. Wong; William L. Ledger (Obstetrics and Gynecology International)
As assisted reproductive technology (ART) methods become the mainstream of infertility treatment, it has become even more critical to reassess its safety. Following the results of a study published by the Robinson Institute in the New England Journal of Medicine, the risk of ART, especially intracytoplasmic sperm injection (ICSI), has never been so closely scrutinized. This paper traces the origins and development of ICSI, assesses the risks documented in the literature, and finally interprets the implications of the study for couples contemplating therapy. We support the need for continued vigilance towards ICSI and the importance in investigating male-factor infertility as a prequel to its use.